DEVELOPMENT STRATEGY OF PHARMACY DEPARTEMENT BASED ACCREDITATION EVALUATION IN RSUD Dr MOEWARDI SURAKARTA BY HANLON METHOD - Ade Sukma Hamdani; Asri Laksmi Riani; Gunawan Pamudji Widodo (Mandala, 2017)
Getting excellent service is the dream of all society, especially recipients of health services in the hospital including in pharmacy departement. Many problems obtained by the patient, because services do not meet the standards. To meet the needs of the patient, pharmacy departement must be accredited. The purpose this study was to determine the suitability of pharmacy departement service to accreditation standards in RSUD Dr Moewardi Hospital Surakarta and development strategy based on Hanlon method. The research was a non experimental research plan. The data collected by using a self-assessment questionnaire of pharmacy care standards. The respondents consisted of key informant was the Hospital Director, Sub Division Head of Human Resources and Training, Head of Organization and Personnel, and the pharmacist in charge, and key informants that pharmacists and pharmaceutical technical employee in pharmacy installation hospital, and the main informant were all pharmacists and pharmacy technical staff of pharmacy installation hospital in Dr Moewardi Hospital Surakarta. From the results count of respondent of pharmacy installation officers, equalled with observation result. The processing of research data conducted with Hanlon method. The results showed that was difference in accreditation standard assessment between self-assessment of pharmacy installation hospital staff (97,5%) with the observation results (93,75%). From this result, the pharmacy installation of Dr Moewardi Surakarta had to meet KARS accreditation standards but still need to be maximized again to lead to JCI accreditation standard. Therefore, it was needed the commitment of Director, Accreditation Committee, Stakeholders and pharmacy installation hospital staffs in improving services in accordance with standards. Strategy and plan development efforts could be done through the addition of pharmacy staff, provision of space/place which meet the standards, complete SOP, optimal pharmaceutical care and evaluated and followed up